Bater em mulher dá cadeia! analise sociocultural da punição na Lei Maria da Penha - Silva, Luciana Santos (2014)
This thesis aims to analyze the effectiveness of the criminal aspects of the Maria da Penha Law, it wonders if its effects were real or symbolic in combating and preventing domestic and family violence against women. The hypothesis that has been confirmed is that its effects are symbolic imprint on the culture of the expansionism of the criminal field. The research was delimited in the region of Vitória da Conquista, Bahia, in the period from 2006 to 2013 and was based on analysis of court cases, interviews and documentary analysis. It was observed that criminal speech does not become effective before the few punishments